SISTEM PENGADAAN BAHAN PUSTAKA PADA DINAS ARSIP DAN PERPUSTAKAAN KOTA BANDUNG - Titin Supriatin; Didik Prata Wijaya (Perpustakaan Nasional RI, 2022)
One of the functions of Department Archives and Libraries of Bandung City is the development and implementation of regional library and archive management which includes library management, archive management and library and archive development. In the management of the library, the role of procuring a collection of library materials is very much needed, especially to increase the reading interest of the people of Bandung. The aim of this study is to determine the system of procurement of library materials, to find out the inhibiting factors in the library material procurement system, and to find solutions from librarians in overcoming obstacles in the procurement of library materials. This research was conducted at Department Archives and Libraries of Bandung City from June to July 2022. This type of research is qualitative research using a descriptive method. The instrument of data collection is by interview, observation, and literature review. The system of procurement of Department Archives and Libraries of the Bandung City is divided into three parts namely procurement selection, procurement process, and procurement result. The steps in the selection process for library materials are surveying user needs, collecting selection tools, and selecting library materials. The Techniques and methods of procurement of library materials with the method of selecting providers by direct procurement by procurement staff. The source of funds for the procurement of library materials comes from the Regional Budget of Bandung City in 2022. The process of receiving library materials includes the activities of examining received library materials, grouping of library materials, and submitting to the library material processing unit. After the procurement process is complete, then proceed to the reporting process. Reports are made periodically in the form of financial realization and performance realization which include procurement methods, number of procurements, types of library materials, and budget sources. difficulties in the procurement of library materials include the limited number of library materials published by publishers, the delay in information from publishers regarding the library materials ordered, and the absence of flexibility in determining the price of library materials. The solution to these obstacles is to communicate more intensely with publishers and seek information on library materials according to the required categories, frequent book fairs, and a more flexible policy of budget adjustment for the procurement of library materials.